Libraries Without Users in Covid-19 Pandemic: Reflection on The Roles of Library and Information Professionals (International Journal of Food and Nutritional Sciences, 2021)
The role of health science librarians in the coronavirus epidemic is examined in this Regular Feature. The global spread of COVID-19 has been fast. Lockdowns have been implemented in all major cities throughout the world. The first case was discovered on March 21st, 2020 in western Maharashtra, and there have been more than 1500 confirmed cases and 12 fatalities since then. An additional 12,000 cases are being investigated throughout the nation. If preventative precautions are not taken, this will only become worse. A curfew has been imposed at all Indian institutions and colleges. University librarians played a critical part in this crisis by educating the general population about the need of good health, assisting medical professionals and researchers, and continuing to provide conventional library services to the residents of western Maharashtra